Sustainability of Rural Electrification Programs Based on Off-Grid Photovoltaic (Pv) Systems in Chile - Cordero-Carrasco, R (Springer Verlag, 2016)
Background: Mainly based on expanding the grid, Chile has reached an impressive electrification rate. However, due to unviable grid expansion to islands and remote areas of the country, the government started implementing off-grid electrification programs. In this paper, we assess the sustainability of rural electrification efforts in Chile paying special attention to off-grid photovoltaic (PV) programs. Methods: Our assessment of the rural electrification efforts in Chile takes into account four dimensions of sustainability (institutional, economic, environmental, and socio-cultural). It is based on an extensive qualitative document analysis, complemented by semi-structured interviews to key stakeholders. Results: We found that, despite several successful pilot off-grid PV projects, the deployment of off-grid PV solutions for rural electrification lagged behind the enormous solar potential of the country. Part of the problem is that decisions favoring other technologies have been made without considering costs over the lifetime and environmental co-impacts. Moreover, the social acceptance of off-grid PV solutions has been seriously compromised due to problems regarding the accuracy (systems were unable to meet the user’s needs) and reliability (systems often failed due to lack of mandatory standards and the uncertain maintenance). Conclusions: Although Chile has conducted remarkable efforts on electrification during the last 20 years, the indigenous communities still have less access to electricity. This disparity is a major drawback that underscores the need for adjusting the electrification approach (which means that the communities or the local authorities have to request electrification at first place) adopted by the Ministry of Energy in rural electrification. Indeed, this approach favors better organized communities leaving behind others—normally the poorest indigenous communities. Moreover, major progress on cultural justice, equity, and environmental awareness is needed for ensuring the sustainability of rural electrification efforts in Chile. © 2016, The Author(s).